2019
DOI: 10.1371/journal.pone.0224193
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate conflict of interest policies at most French teaching hospitals: A survey and website analysis

Abstract: BackgroundThere are 32 teaching hospitals in France, including 30 University hospitals and two Regional teaching hospitals. Teaching hospitals have three roles: health care provision, training of healthcare professionals, and medical research. These roles lead to frequent interactions with pharmaceutical and medical device companies, inevitably raising risks of conflicts of interests. Therefore, policies to manage conflict of interests (COI) are crucial. This study aims to examine COI policies in French teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The authors states that French universities are behind a lot of countries, including the USA. (23,24) Indeed, the American Medical Student Association (AMSA) has been publishing a yearly ranking of American universities since 2007, with much better results.…”
Section: Resultsmentioning
confidence: 99%
“…The authors states that French universities are behind a lot of countries, including the USA. (23,24) Indeed, the American Medical Student Association (AMSA) has been publishing a yearly ranking of American universities since 2007, with much better results.…”
Section: Resultsmentioning
confidence: 99%
“…A Canadian study reported 81% of students being willing to meet with representatives and 75% willing to accept small gifts such as lunches [32]. In Europe, studies have shown that few teaching hospitals in France and almost no medical schools in Germany have comprehensive conflict of interest policies in place [33,34]. In Germany, no medical school reported teaching on conflicts of interest as part of its medical curriculum [34].…”
Section: Box 1 a Case Study Of Industry Interaction With Academic Res...mentioning
confidence: 99%
“…Research to assess how these establishments manage COI with industry would therefore complement the results of our present study. A study in France was carried out to assess COI policies within university teaching hospitals; only 13 out of the 32 major French teaching hospitals had policies covering at least one of the studied criteria [57]. In the United States, AMSA also conducted a survey of COI in university hospitals.…”
Section: Plos Onementioning
confidence: 99%